Fluid‐Mediated Mass Transfer Between Mafic and Ultramafic Rocks in Subduction Zones. (3rd August 2022) - Codillo, E. A.; Klein, F.; Dragovic, B.; Marschall, H. R.; Baxter, E.; Scambelluri, M.; Schwarzenbach‬, E.
Abstract: Metasomatic reaction zones between mafic and ultramafic rocks exhumed from subduction zones provide a window into mass‐transfer processes at high pressure. However, accurate interpretation of the rock record requires distinguishing high‐pressure metasomatic processes from inherited oceanic signatures prior to subduction. We integrated constraints from bulk‐rock geochemical compositions and petrophysical properties, mineral chemistry, and thermodynamic modeling to understand the formation of reaction zones between juxtaposed metagabbro and serpentinite as exemplified by the Voltri Massif (Ligurian Alps, Italy). Distinct zones of variably metasomatized metagabbro are dominated by chlorite, amphibole, clinopyroxene, epidote, rutile, ilmenite, and titanite between serpentinite and eclogitic metagabbro. Whereas the precursor serpentinite and oxide gabbro formed and were likely already in contact in an oceanic setting, the reaction zones formed by diffusional Mg‐metasomatism between the two rocks from prograde to peak, to retrograde conditions in a subduction zone. Metasomatism of mafic rocks by Mg‐rich fluids that previously equilibrated with serpentinite could be widespread along the subduction interface, within the subducted slab, and the mantle wedge. Furthermore, the models predict that talc formation by Si‐metasomatism of serpentinite in subduction zones is limited by pressure‐dependent increase in the silica activity buffered by the serpentine‐talc equilibrium. Elevated activities of aqueous Ca and Al species would also favor the formation of chlorite and garnet. Accordingly, unusual conditions or processes would be required to stabilize abundant talc at high P‐T conditions. Alternatively, a different set of mineral assemblages, such as serpentine‐ or chlorite‐rich rocks, may be controlling the coupling‐decoupling transition of the plate interface. Key Points: Fluid‐mediated mass transfer between mafic and ultramafic rocks can occur from prograde to peak, to retrograde conditions The formation of chlorite‐rich assemblages through Mg metasomatism of mafic rocks is prevalent at high P‐T conditions Talc formation via Si‐metasomatism of serpentinite is more limited in subduction zones than in oceanic plates